The energy spectra of secondary electron emission induced by fast ions - Karas’, V.I.; Kononenko, S.I.; Muratov, V.I. (Вопросы атомной науки и техники, 2001)
It is shown that the distribution function of secondary electrons of ion-induced emission from the front and back surfaces of thin Ag, Cu, Ni foils can be approximated by the power-law function with different power indices in the corresponding energy ranges. The increases of ion energy losses caused the power index to decrease in the first energy interval, while in the second energy interval the power index showed the trend to lessening.